Influence of black phosphorus structural variations for soliton and noise-like pulse generations in an erbium-doped fiber laser - Ng, Eng Khoon; Mohd Yusoff, Norita; Lee, Han Kee; Liew, Josephine Ying Chyi; Omar, Muhammad Firdaus; Zainol Abidin, Nadiah Husseini; Alresheedi, Mohammed Thamer; Mahdi, Mohd Adzir (Elsevier BV, 2024)
We demonstrate black phosphorus (BP) with structural variations of layers (Ls) and quantum dots (QDs) blended with polydimethylsiloxane (PDMS) spin-coated tapered fiber as a light absorbing material for conventional soliton (CS) and noise-like pulse (NLP) generations. Interaction of the evanescent field leads BP materials to exhibit saturable absorption characteristics, with measured modulation depths of 3.50% and 2.12%, respectively. When integrated into an erbium-doped fiber laser cavity, both saturable absorbers (SAs) generated CS pulses initially with durations of 836 fs (BPLs/PDMS-SA) and 1.11 ps (BPQDs/PDMS-SA). At higher pump powers, the pulses switched to NLP with double-scale autocorrelation traces of 283 fs spike on 50 ps pedestal (BPLs/PDMS-SA) and 184 fs spike on 65 ps pedestal (BPQSs/PDMS-SA) due to the optical limiting properties of BP materials. These versatile findings facilitate the potential opportunities of BP-based photonic devices for next generation of ultrafast fiber laser technology with compact and dual functionality.